Indoor Air Quality Performance in Buildings – A Review - Semang, Stewart Sumping; Razali, Mohd Azahari (Journal of Advanced Mechanical Engineering Applications, 2022)
Indoor air quality (IAQ) is the term used to describe the quality of the air within buildings and other structures, particularly as it relates to the wellbeing and comfort of building users. This review covers the fundamentals of the parameters to be measured to determine the IAQ of a building. Reduced risk of indoor health issues can be achieved by understanding and managing common indoor contaminants. Within hours of exposure or perhaps years later, indoor air pollution can have a negative impact on health. Following a single exposure or several exposures to a pollutant, some health consequences such as headaches, dizziness, exhaustion, and irritation of the eyes, nose, and throat may become apparent. Therefore, IAQ assessment must be implemented to measure the parameters according to the standards and guidelines set.